Konsep Honne Tatemae Tokoh Utama dalam Anime Omoi Omoware Furi Furare - Haryanti Oktavia, Devi; Syihabuddin (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2024)
This study is a descriptive qualitative research with a phenomenological approach. The research delves into the concept of Honne-Tatemae used in communication in the anime "Omoi Omoware Furi Furare." The discussion in this study encompasses the application of the Honne-Tatemae concept and its functions within the anime. The data collection technique employed in this research is the note-taking method with descriptive analysis. The findings reveal that the application of Honne-Tatemae in this anime is utilized in various situational contexts, with its functions including avoiding direct conflicts, a desire to maintain social harmony, and self-protection. Keywords: communication; cultural concept; honne tatemae.